Pendampingan Kelompok Ibu Rumah Tangga Sangat Miskin Dalam Upaya Meningkatkan Kesejahteraan Anak di Desa Percut - Eka Kartika Silalahi; Dedi Holden Simbolon (CV. Multi Kreasi Media, 2023)
Percut Village, Percut Sei Tuan District, Deli Serdang Regency is an area with the largest number of people belonging to Very Poor Households (RTSM), namely approximately 1,000 families when compared to other villages in Deli Serdang Regency. From these families, approximately 950 school-age children who have dropped out of school have not even entered formal education. The purpose of Community Service (PKM) is to be able to build a system that can help children from Very Poor Households (RTSM) to get/obtain a minimum education up to high school graduation as well as a view of the importance of health for children and families, because education and Health is a child's capital to achieve a better future. The methods used were (1) providing training and outreach to RTSM mothers, local government and also school-age children about the importance of education and health, (2) providing socialization on how to get free education (scholarships) and government assistance, (3) providing assistance in obtaining educational and health opportunities and information, educational funding assistance, learning process assistance in the form of tutoring and provision of tutoring books up to children graduating from high school, (4) Organizing RTSM mothers and study groups for routine and programmed implementation, thereby building a sustainable system.